PERENCANAAN ARSITEKTUR SISTEM INFORMASI KEIMIGRASIAN PADA PLBN TERPADU DI NTT - Fransiskus Mario Hartono Tjiptabudi (Universitas Boyolali, 2019)
Useful information system to support of business process an organization/company with no eception immigration authority. Business process that so far has been implemented have not use information technology maximally resulted in a fall in the passer the limits for the low service quality to the unfixed data storage and difficulty for finding data and produce reports. The purpose of the research are to design a cross platform information system architecture to support the business process carried out by the immigration authorities on three (3) Integrated Cross Border Posts (PLBN) under the control of the Class II Immigration Office of Atambua, East Nusa Tenggara. For the purposes of the architecture planning was using the framework of TOGAF ADM based on mapped problems, while the design of the information system is based on the PIECES framework. Information systems that proposed aims to solve the problems faced by and to support policy and the government's national strategies in the management of the border region. It is expected that the design of cross platform information system applied to linking immigration offices, immigration officers in PLBN and the passer. The results of this research are expected to be implemented in support of the business process on the immigration authorities with linking immigration offices, immigration officers in PLBN and the passer and also to improve the services of the immigration officer.